Evaluation of morpho-anatomical and chemical differences between varieties of the medicinal plant Casearia sylvestris Swartz - Claudino, Josiane Clarice [UNESP]; Sacramento, Luis Vitor Silva do [UNESP]; Koch, Ingrid; Santos, Helen A. [UNESP]; Cavalheiro, Alberto José [UNESP]; Tininis, Aristeu Gomes; Santos, Andre Gonzaga dos [UNESP] (Academia Brasileira de Ciências, 2013)
Casearia sylvestris Swartz (Salicaceae) é uma planta utilizada na medicina tradicional, cujos extratos de folhas demonstraram importantes ações farmacológicas. A espécie apresenta variação morfológica, genética e química. Duas variedades são consideradas devido a diferenças morfológicas: C. sylvestris var. sylvestris e var. lingua. Há dificuldades na definição destas variedades. O objetivo deste trabalho é avaliar diferenças morfo-anatômicas e químicas entre as variedades de C. sylvestris que permitam sua diferenciação com aplicação farmacêutica ou botânica. Seções transversais e paradérmicas de folhas foram preparadas para análises morfo-anatômicas, histoquímicas e microscopia quantitativa (indices de estômatos e paliçada). Análises cromatográficas (CLAE-DAD e CCD) foram realizadas para obter o perfil de diterpenos clerodânicos. Os resultados das análises morfo-anatômicas demonstraram diferenças significativas entre as variedades somente em cortes paradérmicos: var. sylvestris - paredes celulares epidérmicas poligonais e hipoestomática, var. lingua - paredes celulares epidérmicas arredondadas e anfiestomática. Os índices de estômatos não revelaram diferenças; os valores dos índices de paliçada foram de 2,8 para var. lingua e 3,9 para var. sylvestris. As análises cromatográficas confirmaram resultados prévios, demonstrando predomínio de diterpenos na var. sylvestris. Este trabalho sugere que análises cromatográficas e morfo-anatômicas podem ser ferramentas aplicáveis na distinção das variedades da espécie.

Casearia sylvestris Swartz (Salicaceae) has been used in traditional medicine and its leaf extracts have been exhibited important pharmacological activities. The species presents morphological, chemical and genetic variation. Two varieties are considered due external morphological differences: C. sylvestris var. sylvestris and var. lingua. There are difficulties in definition of these varieties. The objective of this work is to evaluate chemical and morpho-anatomical differences between C. sylvestris varieties that can be applied in their distinction for pharmaceutical or botanical purposes. Transverse and paradermic sections of leaves were prepared for morpho-anatomical, histochemical and quantitative microscopy (stomatal and palisade index) analyses. Diterpene profiles of the specimens were obtained by HPLC-DAD and TLC. Morpho-anatomical analyses demonstrated significant differences between the varieties only in paradermic sections: var. sylvestris - polygonal epidermic cell walls and hypostomatic; var. lingua - rounded epidermic cell walls and amphistomatic. No differences were observed for stomatal index; palisade index was found 2.8 for var. lingua and 3.9 for var. sylvestris. Chromatographic analyses confirmed previous results demonstrating that diterpene profile in varieties differs, with predominance of these metabolites in var. sylvestris. In conclusion, this work indicates that chromatographic analysis besides morpho-anatomical analysis can be applied in distinction of C. sylvestris varieties.
Keywords: Casearia sylvestris; cromatografia; diterpenos; morfo-anatomia; Casearia sylvestris; chromatography; diterpenes; morpho-anatomy